Design of Car Heat Remover Based on Product Design and Development Methodology - Taufik, Roni Sahroni; Hambali, Arep@Ariff; Tajul Ariffin , Abdullah; Md Dan, Md Palil (Penerbit UTeM, 2011)
The greenhouse effect causes high temperatures inside the passenger cabin. The interior of a car can be much warmer than the outside air because when the sun hits the windshield the incoming shortwave radiation hits the windshield then passes through the windshield to come out as long wave (heat energy) radiation on the inside of the car. This long wave radiation is now trapped inside the car because the windshield will not allow the long wave radiation to escape back through the windshield and as a result heat builds up inside the car. Vehicle interior temperature increases after long hours under the sunlight. Conventional car heat removal device is under the hood, which is not significant to reduce the air temperature inside of car. This project presents the new design of car heat remover by applying Latent Energy Storage (LES). The benefits of this product are to control vehicle internal temperature and to protect the vehicle’s interior from damage due to high temperature. A car heat remover is a device designed for the purpose of reducing the surrounding high temperature to a cooler temperature in the interior of a vehicle. With the car heat remover, when the equilibrium state in the interior of the car is reached, the heat will be absorbed and the absorbed heat will then pass through the vents in the device and come in contact with a LES placed inside the device. The heat will then be condensed and converted to a cooler air and dissipate to the surrounding interior. As a result, a new design of car heat remover using latent energy storage was developed.